PENCEMARAN AIR DAN DAMPAKNYA TERHADAP DUNIA PERIKANAN - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2008)
AbstractHuman with the environments shall can run adjoining. Development is one of human effort to be able increase the life prosperity, but development do not mean must disregard environmental ability in sustaining it. Environmental pollution as product from development will affect again human as development agent.Keyword: Development, environmental pollution, human.